Gender Responsive Classroom Management to Prevent Bullying during Puberty in Elementary School Students - Fitrani, Nurokhmah; Suryanti, Suryanti; Widodo, Wahono (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to strive for gender-responsive classroom management in elementary schools so that it can minimize and prevent bullying among elementary school students. During puberty, sensitivity to gender, self-identity, and social pressure increases, and ignorance of sex education and the reproductive system makes students more vulnerable to bullying. This research uses the systematic literature review (SLR) method by collecting literature from scientific journals, books, and other sources. The results of this research are strengthened by students' knowledge about sexuality education and the reproductive system, thereby making students' attitudes able to accept differences and demonstrate behavior that supports gender equality. Based on this research, it was concluded that classroom management, which focuses on gender-responsive matters in facing puberty, has been proven to be able to minimize and prevent bullying in elementary school students. Gender-responsive classroom management has great potential to prevent bullying and create a safer and more inclusive learning environment for all students. The implications of this research cover various aspects, from curriculum development and teacher training to changes in social norms. By applying these research findings, we can create a generation of young people who are more equal, tolerant, and respectful of differences.